(untitled) (Jurnal Sosial Ekonomi Pertanian, 2021)
The objectives of this study are: (1) Describe the implementation of outreach in distributing information about the ISPO concept. (2) Analyzing the role of extension services in the preparation of oil palm replanting by independent smallholders according to the ISPO concept in Rokan Hulu Regency. The sampling method used was the multistage sampling method with 90 independent oil palm farmers taken as respondents. Descriptive data analysis and using a Likert scale. The results showed: Extension in Rokan Hulu Regency did not go well. On average, the role of extension is less of a role in providing education, dissemination of information, facilitation, consultation, supervision, and monitoring evaluation to independent patterned oil palm farmers, so that farmers are less independent in implementing ISPO